Pembuatan Peta Situasi Skala 1:500 Desa Beluk dan Desa Banyuripan Kecamatan Bayat Kabupaten Klaten Provinsi Jawa Tengah - , M ALDIN YUSFAN ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This thesis aims to provide information on the results of Job Training (PKL) for making maps of situation at Beluk and Banyuripan village, Bayat, Klaten, Central Java. Resulting the maps situation on scale of 1: 500 were processed digitally. Measurements were made directly in the field using a measuring instrument such as Total Station, Waterpass for leveling and other tools as well as a variety of software for processing measurement data, so can be processed and displayed in the form of maps situation on large-scale, that the scale is 1: 500. From this practice can be concluded that the activities of the Job Training is able to give more experience to the students to enhance the appreciation, ability and skills of the students in carrying out all the activities of the mapping.